Life Skills in a Minute: Ironing Versus Pressing - Heather M. Janney (EDIS)
The words pressing and ironing are often interchanged. However, these two terms are not equivalent. Ironing is what you do to remove wrinkles by sliding a hot iron back and forth. Pressing is the process of lifting and putting the iron down on a specific part of a project. When learning to sew, it is important to know the difference. This new 3-page publication of the UF/IFAS 4-H Youth Development program details the difference in these concepts. Written by Heather Janney. https://edis.ifas.ufl.edu/4h415